Experimental Study on the Evolution of Argillization of Mudstone and Cutter Wear during the TBM Tunnelling - Kanglei Song; Bolong Liu; Haiqing Yang (Shock and Vibration)
Argillization is a process in which clay-bearing rocks disintegrate into the clay under the action of high temperature, pressure, and water. When tunnel boring machines (TBMs) excavate in the mudstone, argillization takes place, causing the clogging of the TBM cutterhead. As a result, the penetration rate drops gradually. Abnormal wear might occur. To investigate the evolution of argillization of mudstone and cutter wear during the TBM tunnelling, a series of rotary indentation tests were carried out on the self-designed experimental bench for different loading times. During the test, the temperature and penetration depth of disc cutters were measured in real time. After loading, microstructures of cutting grooves, slacking mudstone, and worn cutter ring were observed by stereomicroscope. Consequently, the evolution of argillization in mudstone and cutter wear were investigated. Experimental results indicate that the argillization process of mudstone by disc cutter can be divided into three stages: mechanical cutting stage, deterioration of mudstone and the formation of slacking mudstone stage, and adherence of slacking mudstone stage. Specifically, at mechanical cutting stage, the rock was cut by cutter directly, causing high frictional heat. Then the microstructure of mudstone was deteriorated due to the water-weakening mechanisms, temperature effect, and mechanical activation effect. Finally, the slacking mudstone was adhered to the disc cutter. Correspondingly, due to the argillization of mudstone, the disc cutter wear goes through the mechanical wear stage, argillization wear stage, and secondary wear stage in sequence. This investigation reveals the rock cutting mechanism of TBM considering the argillization of mudstone. Furthermore, it provides some references for design and operation of the TBM.